Aplicações dos números complexos à geometria analítica plana - Vieira, José Fernando Gaudêncio (2018)
This dissertation has as main objective to provide some different applications of complex numbers in the study of at geometry. We started with a bit of the history of complex numbers, and answer frequently asked questions. by high school students when this content is introduced, followed by the operational concepts required for applications. Next, content of the analytical geometry that will be used later. Lastly, we arrive at the main objective, dealing with the applications of the complex numbers in the geo- model, reformulating results and concepts of analytical geometry and providing applications in the study of triangles and polygons in general.